PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL PADA INDEKS PEMBANGUNAN MANUSIA - Williantara, Gede Ferdi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aims to determine the influence of local revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the Human Development Index (HDI). This study uses a sampling saturated, with a total sample of 45 observations. The data used is Local Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Capital Expenditure, and the Human Development Index which is derived from the realization of the budget and the report's Human Development Index Table Regency / City in the province of Bali in 2009- 2013. This study uses multiple linear regression analysis. The results of this study indicate that the PAD, DAU, and DBH don’t affect the Human Development Index. This indicates that the ability of PAD, DAU and DBH finance capital expenditures does not affect the achievements of IPM. However, the Special Allocation Fund showed a negative effect on the results of the IPM. This indicates that the greater the DAK in financing the capital expenditure will be able to lower the HDI achievement.
Keywords: Local Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Human Development Index